2011
DOI: 10.1038/npp.2011.26
|View full text |Cite
|
Sign up to set email alerts
|

Latent Inhibition-Related Dopaminergic Responses in the Nucleus Accumbens are Disrupted Following Neonatal Transient Inactivation of the Ventral Subiculum

Abstract: Schizophrenia would result from a defective connectivity between several integrative regions as a consequence of neurodevelopmental failure. Various anomalies reminiscent of early brain development disturbances have been observed in patients' left ventral subiculum of the hippocampus (SUB). Numerous data support the hypothesis of a functional dopaminergic dysregulation in schizophrenia. The common target structure for the action of antipsychotics appears to be a subregion of the ventral striatum, the dorsomedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 99 publications
3
27
0
Order By: Relevance
“…The cannula was left in the PFC for 4 min after the end of the microinjection to allow PBS and TTX to diffuse in the targeted structure. The amount of TTX microinjected in the PFC (100 mM Â 0.3 ml), approximately 10 ng, is similar to that reported previously in the literature (Zhuravin and Bures, 1991;Peterschmitt et al, 2007;Meyer et al, 2009;Meyer and Louilot, 2011). It has been reported that the effects resulting from the TTX blockade last 24-48 h (Rothfeld et al, 1986).…”
Section: Surgerysupporting
confidence: 82%
See 4 more Smart Citations
“…The cannula was left in the PFC for 4 min after the end of the microinjection to allow PBS and TTX to diffuse in the targeted structure. The amount of TTX microinjected in the PFC (100 mM Â 0.3 ml), approximately 10 ng, is similar to that reported previously in the literature (Zhuravin and Bures, 1991;Peterschmitt et al, 2007;Meyer et al, 2009;Meyer and Louilot, 2011). It has been reported that the effects resulting from the TTX blockade last 24-48 h (Rothfeld et al, 1986).…”
Section: Surgerysupporting
confidence: 82%
“…Recent evidence from in vivo animal studies backs the existence of a differential involvement of dopaminergic neurons innervating the core and dorsomedial shell subregions of the nucleus accumbens in this phenomenon (Jeanblanc et al, 2002;Louilot et al, 2010). Moreover, as shown recently, unilateral neonatal functional blockade in the left hemisphere of two temporal regions linked to the PFC, the entorhinal cortex, or the ventral subiculum of the hippocampus (Jay and Witter, 1991;Hoover and Vertes, 2007) have been found to be sufficient to induce a disruption of the behavioral manifestation of latent inhibition and the latent inhibition-related dopaminergic variations in adult animals, with a differential reversal of these responses in the left core part of the nucleus accumbens (Peterschmitt et al, 2007;Meyer and Louilot, 2011).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations